Community intervention in the societal inequity of women's political participation: The development of efficacy and citizen participation in rural Nicaragua. Issue 4 (1st October 2020) - Grabe, Shelly; Dutt, Anjali
Abstract: Globally, limited opportunities for women's political participation and decision-making reflect a widespread societal problem perpetuated through gender inequities that operate at numerous levels of society. Challenging and ending systemic gender-based power imbalances is critical to understanding the potential for women's political participation. The current study uses a liberation psychology approach to examine how a community intervention interrupts traditional gender ideology, enhances women's agency and political efficacy, and increases civic engagement and community leadership among women in rural Nicaragua. Research was conducted in partnership with a grassroots women's organization and data were taken from 261 surveys. Findings suggest that community-level interventions interrupt standard notions of women's political participation, resulting in greater agency and efficacy and thereby higher levels of decision-making and leadership. The findings illustrate the importance of assessing the psychosocial processes involved in transformative political spaces that facilitate women's meaningful citizen engagement, having important implications for women's political participation worldwide.